The kinetics of X + H2 reactions (X = C(1D), N(2D), O(1D), S(1D)) at low temperature: recent combined experimental and theoretical investigations. Issue 4 (2nd October 2021) - Hickson, Kevin M.; Larrégaray, Pascal; Bonnet, Laurent; González-Lezana, Tomás
ABSTRACT: In recent years, combined experimental and theoretical efforts have brought valuable information on the kinetics of reactive collisions between molecular hydrogen and an electronically excited atom X (where X = C ( 1 D ), N ( 2 D ), O ( 1 D ) or S ( 1 D ) ). These four reactions have been comparatively studied together in numerous occasions in the past due to the similar importance of complex-forming mechanisms found in their overall dynamics. In this work, we compile the most updated information on these investigations making a special emphasis from the theoretical side on statistically based techniques, in an attempt to test the possible insertion nature of the overall dynamics. Besides a description of the experimental details of the kinetics investigation, a comparison of the measured rate constants over a temperature range between 50 and 300 K with the most recent theoretical calculations is presented.